Silk Fibroin Nanoparticles for Enhanced Cuproptosis and Immunotherapy in Pancreatic Cancer Treatment - Si Gao; Haodong Ge; Lili Gao; Ying Gao; Shuibin Tang; Yiming Li; Zhiqing Yuan; Wei Chen (Advanced Science)
Abstract Cuproptosis is a newly discovered copper ion‐dependent programmed cell death. Elesclomol (ES) is a Cu2+ transporter that delivers Cu2+ into tumor cells, causing cell death at toxic doses. However, ES has a short blood half‐life, limiting its accumulation in tumors. This study introduces Tussah silk fibroin nanoparticles (TSF@ES‐Cu NPs) to protect ES and Cu2+. TSF, with a stable structure, resists metabolism in circulation. Targeting tumors with natural RGD peptides and TSF's unique secondary structure, enhances drug enrichment and special release in pancreatic tumors, improving treatment efficacy. In vitro, TSF@ES‐Cu induces tumor cell cuproptosis, releases DAMPs, promotes dendritic cells (DCs) maturation, and macrophage M1 polarization. In vivo, TSF@ES‐Cu reshapes the tumor microenvironment (TME), increasing mature DCs from 22.7% to 43.3%, CD8+ T cells from 5.08% to 17.1%, and reducing M2 macrophages from 50.7% to 18.4%. Additionally, the combined anti‐tumor efficacy of TSF@ES‐Cu and αPDL‐1 is 1.6 times higher than TSF@ES‐Cu alone and 2.5 times higher than αPDL‐1 alone. In summary, this study reports that the combination of TSF@ES‐Cu and αPDL‐1 effectively induces cuproptosis and reshapes the TME, offering a new approach for copper nanomaterial‐based tumor immunotherapy.